Development of a Dating Violence Assessment Tool for Late Adolescence Across Three Countries: The Violence in Adolescents' Dating Relationships Inventory (VADRI). Issue 17 (September 2017) - Aizpitarte, Alazne; Alonso-Arbiol, Itziar; Van de Vijver, Fons J. R.; Perdomo, Maria Cristina; Galvez-Sobral, J. Andres; Garcia-Lopez, Eric
Accurate assessment of dating violence (DV) is crucial for evaluation and intervention planning. However, extant self-report measurement tools of DV do not adequately consider age-, generation-, and culture-specific issues, which are essential for its accurate conceptualization. To address these gaps, we developed the Violence in Adolescents' Dating Relationships Inventory (VADRI) and evaluated its psychometric properties. The VADRI was developed based on a qualitative approach for item development through adolescents' individual interviews, focus groups, and experts' judgments, followed by a quantitative approach for tool assessment. Two aspects of DV were addressed: victimization and perpetration. After the necessary cultural and linguistic adaptation of items, the instrument was administered to 466 adolescents from three Spanish-speaking countries: Guatemala, Mexico, and Spain. The items were best represented by a one-factor solution in each country, which suggests that DV is a unidimensional construct combining victimization and perpetration. Analyses of item-level factor weights and differential item functioning were conducted aimed at obtaining information about items that best represented the construct, resulting in a 26-item final version that was cross-culturally equivalent. Convergent validity was supported by positive correlations with the Conflict in Adolescent Dating Relationships Inventory, and reliability analyses yielded favorable results (with all Cronbach's α values above .90). We conclude that the VADRI is a valid and reliable instrument for the assessment of DV in various cultural contexts.